(untitled) (Journal of the College of Basic Education, 2026)
This research aims to determine the impact of an instructional-learning design based on metacognitive strategies on the mathematics achievement and visual thinking of fifth-grade science students. To achieve this, the researcher used the experimental method and adopted a quasi-experimental design with two equivalent groups and a post-test, the control groupThe researcher defined the research population as fifth-grade science students in preparatory and secondary schools for boys affiliated with the General Directorate of Education in Baghdad/Al-Rusafa Third District, Qutaiba Preparatory School for Boys was intentionally chosen as a sample for the current research from among the schools in the research population, which included (4) sections, two of which were selected by random drawing, Section (B) represented the experimental group with (33) students, and section (C) represented the control group with (36) students. The two groups were matched on the variables of (intelligence, prior knowledge, chronological age calculated in months, prior achievement, and visual thinking), The researcher defined the curriculum content and formulated (140) behavioral objectives according to Bloom’s cognitive levels. The achievement test adopted by (Mahr, 2018), which consists of (35) items, including (30) objective multiple-choice items and (5) essay items, with a weight of (50) points, was considered a visual thinking test consisting of (18) multiple-choice items, Validity and reliability were verified using appropriate statistical methods, The results showed that the experimental group students outperformed the control group students in the variables of achievement and visual thinking, In light of the research findings, the researcher made several recommendations and proposed a set of further suggestions